Online Purchasing Behavior of Generation Y Consumer in Northeast Thailand - Jinarat, Veerasak (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This quantitative research is intended to study online purchasing behavior of generation Y consumers in northeast of Thailand, including the mean comparative and rational relationship analysis for further development. The researcher developed a 23-item questionnaire and collected from 348 volunteers. The statistics analysed were frequency, percentage, means, standard deviation, t-test, F-test, MANOVA and linear regression analysis. The results present that the mean of consumer behavior and intention behavior are high for all components. Besides, the mean difference of consumer behavior and intention behavior also contributed statistically significant difference at .05, separated by age, education, occupation, time-used for online media and online purchasing product. Importantly, this research demonstrates that the development of online purchasing for generation Y, the online entreprenure must offer the diversity of mass virtual products with the information to ensure the trust, confidence, and perceived usefulness in purchasing products.